Pengaruh Strategi Pembelajaran Peningkatan Kemampuan Berpikir (SPPKB) Terhadap Kemampuan Menulis Teks Eksplanasi Siswa Kelas XI SMK Swasta Teladan Pematangsiantar - Leonardo Damanik (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The purpose of this research is “ To determine the effect of the Thinking Ability Improvement Learning Strategy (SPPKB) on the Ability to Write Explanatory Texts for Class XI Students of Pematangsiantar Exemplary Private Vocational School in the 2021/2022 Academic Year”. The hypothesis in this study is “There is a significant effect of Thinking Skills Improvement Learning Strategy (SPPKB) on the Ability to Write Explanatory Texts in class XI of Pematangsiantar Exemplary Private Vocational School in the Academic Year 2021/2022”. The subjects in this study were students of class XI of class XI SMK Private Teladan in the Academic year 2021/2022, totaling 240. The sample was taken by purposive sampling and obtained class XI AKL 2 with a total of 23 students as the class that was used as experimental research or as a class that was influenced by learning strategis for improving thinking skills (SPPKB). The data was then analyzed using test at a significance level of 5%. The results of the test calculations carried out on the pre-test scores showed that there was a significant difference in the ability to write explanatory texts before and after using the influence of SPPKB (Learning Strategis for Improving Thinking Skills). After the pre-test and post-test, it is seen that the difference in avarage after SPPKB effect is applied is greater than before the SPPKB effect is applied. The increase in the post-test avarage (82,56)was higher than before the pre-test was apllied to learning the effect of SPPKB (72.91). there for it can be concluded that the effect of SPPKB is effectively used in learning to write axplanatory texts for class XI at Pematangsiantar Private Vocational Highs School, so it can be said that the learning process is said to be succesfull.